The role of patent waivers and compulsory licensing in facilitating access to COVID-19 vaccines: Findings from a survey among healthcare practitioners in Nigeria. - Obi Peter Adigwe; Davidson Oturu (Public Library of Science (PLoS), 2022)
The roll out of COVID-19 vaccines has again revealed the gap between high income countries and developing nations in terms of access to healthcare commodities and services. With the slow vaccination roll out in many low income countries and the emergence of more contagious variants of COVID-19, many persons are at risk of contracting the disease in settings with low immunisation coverage. This study aimed at exploring the views of healthcare practitioners on the role of patent waivers and compulsory licensing in facilitating access to vaccines. A cross-sectional study was undertaken among practitioners in the health sector, which comprised private, public, and development agencies. A well structured and validated questionnaire was administered to the study participants using both physical and online methods of administration in Nigerian setting. A total of 526 respondents participated in the study, majority of them were males (54.4%). A third of the study participants (31.1%) had postgraduate degrees. A strong majority of the respondents (81.2%) agreed that the role of patent is to promote innovation, whilst 70.6% of them indicated that intellectual property waivers can improve access to COVID-19 vaccines. Slightly above half of the respondents (56.0%) indicated that patent waivers can reduce innovation in the pharmaceutical sector, they however indicated that such challenge can be mitigated by granting incentives to innovators whose intellectual property rights had been waived. This study has revealed that there is a need for intellectual property rights waiver and compulsory licensing of all novel COVID-19 commodities including vaccines, as this is an important strategy that can improve access to relevant products in developing countries.